Use of JAK Inhibitors in Lichen Planus: An Update - Dario Didona; Raffaele Dante Caposiena Caro; Laura Calabrese; Martina D’Onghia; Giulia Galluccio; Matteo Riccardo Di Nicola; Alessandra Rallo; Giovanni Paolino (Medicina, 2025)
Lichen planus (LP) is a chronic inflammatory disorder affecting approximately 1% of the population. It presents with a wide range of clinical manifestations, mainly involving the skin, mucosal surfaces, and skin appendages, and is often characterized by a relapsing course and variable response to treatment. Although several therapeutic strategies are available, many are off-label and show limited efficacy in resistant forms. Increasing evidence points to the central role of the JAK/STAT signaling pathway in the immunopathogenesis of LP, with cytokines such as interferon-gamma and interleukin-21 playing key roles in sustaining chronic inflammation. Based on this rationale, Janus kinase (JAK) inhibitors have recently been proposed as potential therapeutic agents in LP. This review explores the biological basis for their use and systematically summarizes the existing clinical evidence on the use of JAK inhibitors in cutaneous, mucosal, appendageal, and nail variants of LP. The preliminary data suggests favorable outcomes in many patients with difficult-to-treat disease, with an acceptable safety profile. Further prospective trials are needed to establish their definitive role in the management of LP.